Dynamic Matrix Control and Tuning Parameters Analysis for a DC Motor System Control - Ndje, M.; Nyobe Yome, J. M.; Boum, A. T.; Bitjoka, L.; Kamgang, J. C. (Engineering, Technology & Applied Science Research, 2018)
Model predictive control (MPC) in system control industry overrides the challenges of conventional controllers in controlling complex systems. However, for efficient control, it is essential to find the best combination of parameter values. In this paper, we present the implementation of a multivariable dynamic matrix control (DMC) algorithm. An industrial system consisting of a DC motor, coupled to a mechanical load, the assembly associated with an electronic speed variator was considered to test the implemented DMC controller. DMC’s tuning parameter analysis on the manipulated inputs and their variations on the controlled outputs was performed. Results guarantee that efficient control was presented.